Natural Fibrous Materials as Eco-Friendly Air Filters - Seokhyun Chin; Woori Choi; Sunghwan Jung (Journal of Natural Fibers)
Exposure to particulate matter has various health consequences, and high-efficiency particulate air (HEPA) filters and facial masks are used to remove such pollutants. However, these have issues of producing microplastics, being environmentally unfriendly, and sometimes expensive. This study aims to discover the potential of recycling natural fibrous materials as an environmentally friendly and cost-effective alternative to plastic-based filters. Various fibers – carbonized rice husks (CRH), rice husks (RH), sugarcane bagasse (sugarcane), and coconut fibers – are characterized by their filtration performance, tensile strength, wettability, and morphology. The quality factors were 12.4 X10−3, 8.48 X10−3, 7.53 X10−3, 5.21 X10−3, 6.46 X10−3, and 1.15 X10−3 for HEPA, facial mask, CRH, RH, sugarcane, and coconut fiber filters, respectively. The tensile strengths (MPa) were 69.3 X10−2, 82.6 X10−2, 32.7 X10−2, 25.5 X10−2, 102 X10−2, and 87.2 X10−2 of HEPA, dental mask, CRH, RH, sugarcane, and coconut fiber filters, respectively. HEPA filters performed best, though their materials were made from non-biodegradable materials. CRH and dental masks were second best, with both maintaining a similar level of performance. Overall, CRH demonstrated the highest potential as an air filtration media of the natural fibrous materials.